Psychometric properties and meaningful change thresholds for the QOL-E instrument in patients with myelodysplastic neoplasms - Oliva, Esther Natalie; Guo, Shien; Lord-Bessen, Jennifer; Yucel, Aylin; Latagliata, Roberto; Breccia, Massimo; Palumbo, Giuseppe A.; Sanpaolo, Grazia; Riva, Marta; Santini, Valeria; Platzbecker, Uwe; Garcia-Manero, Guillermo; et al. (Frontiers in Oncology, 2025)
BackgroundMyelodysplastic neoplasms (MDS) are characterized by ineffective hematopoiesis, peripheral blood cytopenias, and an increased risk of progression to acute myeloid leukemia. One of the main treatment goals is improving quality of life (QoL), particularly for patients with lower-risk MDS (LR-MDS) who may live longer with compromised QoL. The QOL-E© is a patient-reported outcome (PRO) measure specifically developed to address the lack of a health-related QoL questionnaire for patients with MDS. The objective of this study was to evaluate the psychometric performance of the QOL-E in patients with LR-MDS.MethodsData from four clinical trials in MDS (MEDALIST, DARB-MDS, EQoL-MDS, and RevMDS trials) were used to assess construct validity, reliability, and responsiveness. The QOL-E was validated by the European Organization for the Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire – Core 30 (QLQ-C30) and clinical outcomes. It contains 29 items with the first two items assessing the patient’s general well-being and the 27 remaining items grouped into six domain scores: physical well-being (QOL-FIS), functional well-being (QOL-FUN), social/family well-being (QOL-SOC), sexual well-being (QOL-SEX), fatigue (QOL-FAT), and MDS-specific disturbances (QOL-MDSS). Additionally, meaningful within-patient change (MWPC) thresholds were determined for the domains and summary scores of the QOL-E using anchor-based analyses, supported by distribution-based analyses.ResultsA total of 458 patients were included in the analyses. The QOL-E domain/summary scores demonstrated acceptable convergent/divergent and known-groups validity. Test-retest reliability and internal consistency was confirmed with intraclass correlation coefficients and Cronbach alpha exceeding 0.70 across most QOL-E domains/summary scores. The QOL-E domains/summary scores, except for QOL-SEX, had an adequate ability to detect change from baseline to Week 24. MWPC thresholds were proposed for all other domains and summary scores.ConclusionThe study results demonstrate that the QOL-E is generally fit for purpose to assess treatment effects in populations with LR-MDS and the proposed MWPC thresholds can be used to assess within-patient treatment effect on PROs, as assessed by the QOL-E, in future studies.